2021
DOI: 10.1017/s1041610221000296
|View full text |Cite
|
Sign up to set email alerts
|

Reopening the doors of Dutch nursing homes during the COVID-19 crisis: results of an in-depth monitoring

Abstract: Objectives: On May 11, the Dutch Government allowed 26 nursing homes to welcome 1 visitor per resident, after 2 months of lockdown. The study aimed to monitor in-depth the feasibility of the regulations and their impact on the well-being of residents, their visitors, and healthcare staff. Design: Mixed-methods study in 5 of the 26 facilities; the facilities were affiliated to an academic network of nursing homes. Participants: Visitors and healthcare professionals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…We saw a great variety in how nursing homes dealt with COVID-19 infections. While the Dutch government recommended that no more national visiting bans in nursing homes should be implemented [9], nearly half of the respondents indicated that they would close whole nursing home wards for visitors in case of an infection. A minority of the nursing homes would close the whole nursing home for visitors if there was an infection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We saw a great variety in how nursing homes dealt with COVID-19 infections. While the Dutch government recommended that no more national visiting bans in nursing homes should be implemented [9], nearly half of the respondents indicated that they would close whole nursing home wards for visitors in case of an infection. A minority of the nursing homes would close the whole nursing home for visitors if there was an infection.…”
Section: Discussionmentioning
confidence: 99%
“…Already early in the pandemic (spring/summer 2020), nursing homes were at the "end of the line" [4] with regard to national allocation of COVID-19 tests and personal protective equipment. For personal protective equipment, the shortage appears to have resolved compared to the period May-June 2020 [9]. Respondents were most concerned about the impact of this second wave on staff.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations